Hypothalamic carnitine metabolism integrates nutrient and hormonal feedback to regulate energy homeostasis. (15th December 2015) - Stark, Romana; Reichenbach, Alex; Andrews, Zane B.
Abstract: The maintenance of energy homeostasis requires the hypothalamic integration of nutrient feedback cues, such as glucose, fatty acids, amino acids, and metabolic hormones such as insulin, leptin and ghrelin. Although hypothalamic neurons are critical to maintain energy homeostasis research efforts have focused on feedback mechanisms in isolation, such as glucose alone, fatty acids alone or single hormones. However this seems rather too simplistic considering the range of nutrient and endocrine changes associated with different metabolic states, such as starvation (negative energy balance) or diet-induced obesity (positive energy balance). In order to understand how neurons integrate multiple nutrient or hormonal signals, we need to identify and examine potential intracellular convergence points or common molecular targets that have the ability to sense glucose, fatty acids, amino acids and hormones. In this review, we focus on the role of carnitine metabolism in neurons regulating energy homeostasis. Hypothalamic carnitine metabolism represents a novel means for neurons to facilitate and control both nutrient and hormonal feedback. In terms of nutrient regulation, carnitine metabolism regulates hypothalamic fatty acid sensing through the actions of CPT1 and has an underappreciated role in glucose sensing since carnitine metabolism also buffers mitochondrial matrix levels of acetyl-CoA, an allosteric inhibitor of pyruvate dehydrogenase and hence glucose metabolism. Studies also show that hypothalamic CPT1 activity also controls hormonal feedback. We hypothesis that hypothalamic carnitine metabolism represents a key molecular target that can concurrently integrate nutrient and hormonal information, which is critical to maintain energy homeostasis. We also suggest this is relevant to broader neuroendocrine research as it predicts that hormonal signaling in the brain varies depending on current nutrient status. Indeed, the metabolic action of ghrelin, leptin or insulin at POMC or NPY neurons may depend on appropriate nutrient-sensing in these neurons and we hypothesize carnitine metabolism is critical in the integrative processing. Future research is required to examine the neuron-specific effects of carnitine metabolism on concurrent nutrient- and hormonal-sensing in AgRP and POMC neurons. Highlights: CPT1a and 1c in neurons in the hypothalamic arcuate nucleus control energy and glucose homeostasis. The hypothalamic carnitine genes carnitine palmitoyl transferase 1a and 1c simultaneously integrate nutrient and hormonal cues. The metabolic action of hormones such as insulin, leptin and ghrelin require appropriate integration of nutrient cues via carnitine metabolism.